2018
DOI: 10.1111/trf.14592
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to the outcome of prophylactic platelet transfusions in patients with hematologic malignancies: an observational study

Abstract: Transfusion outcomes were significantly related to several PC-related factors. Associations for ABO matching status and storage duration were stronger than previously reported. Taking into account such factors when selecting a PC for transfusion could be beneficial to the recipient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Major mismatched platelet transfusions promote clearance of transfused platelets, lowering the CCI, 7–9 decreasing the efficacy of the transfusion, and shortening the time for a subsequent platelet transfusion, thus increasing the demand for platelet transfusions. Two previous studies 7,8 found a 4–5 h decrease in the platelet transfusion interval for those who received an ABO major mismatched platelet transfusion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Major mismatched platelet transfusions promote clearance of transfused platelets, lowering the CCI, 7–9 decreasing the efficacy of the transfusion, and shortening the time for a subsequent platelet transfusion, thus increasing the demand for platelet transfusions. Two previous studies 7,8 found a 4–5 h decrease in the platelet transfusion interval for those who received an ABO major mismatched platelet transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Major mismatched platelet transfusions promote clearance of transfused platelets, lowering the CCI, 7–9 decreasing the efficacy of the transfusion, and shortening the time for a subsequent platelet transfusion, thus increasing the demand for platelet transfusions. Two previous studies 7,8 found a 4–5 h decrease in the platelet transfusion interval for those who received an ABO major mismatched platelet transfusion. Similarly, we found an increased requirement for a subsequent platelet transfusion for recipients of a major mismatched platelet transfusion with 20% increased odds of receiving another platelet transfusion within 2 days.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although transfusion of ABO-identical platelet concentrate (PC) is widely recognized as the most effective and safest therapeutic strategy its widespread use is not always possible. 1 For this reason, a vast majority of blood banks enable the transfusion of non-identical PCs, especially the ones obtained through apheresis from group O donors to non-O recipients. Such PCs pose a risk of posttransfusion hemolytic reaction, which may be especially intense in group A recipients.…”
Section: Introductionmentioning
confidence: 99%